Search for new resonances decaying via WZ to leptons in proton-proton collisions at root s=8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Ero, J.; Fabjan, C.; Friedl, M.; Fruhwirth, R.; Ghete, V. M.; Hartl, C.; et al. (Elsevier B.V., 2015)
A search is performed in proton-proton collisions at root s = 8 TeV for exotic particles decaying via WZ to fully leptonic final states with electrons, muons, and neutrinos. The data set corresponds to an integrated luminosity of 19.5 fb(-1). No significant excess is observed above the expected standard model background. Upper bounds at 95% confidence level are set on the production cross section of a W boson as predicted by an extended gauge model, and on the W'WZ coupling. The expected and observed mass limits for a W' boson, as predicted by this model, are 1.55 and 1.47 TeV, respectively. Stringent limits are also set in the context of low-scale technicolor models under a range of assumptions for the model parameters. (C) 2014 The Authors. Published by Elsevier B.V.
Keywords: CMS; Physics; Technicolor